2012
DOI: 10.1021/jp304314j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Studies of Base-Catalyzed Phenylselenoetherification of (Z)- and (E)-Hex-4-en-1-ols

Abstract: The mechanism of phenylselenoetherification of (Z)- and (E)-hex-4-en-1-ols using some bases (triethylamine, pyridine, quinoline, 2,2'-bipyridine) as catalysts and some solvents [tetrahydrofuran (THF) and CCl4] as reaction media was examined through studies of kinetics of the cyclization by UV-vis spectrophotometry. It was demonstrated that the intramolecular cyclization is facilitated in the presence of bases as a result of the hydrogen bond between the base and the alkenol's OH group. The rate constants in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In accordance with earlier findings [18,19], the distance between the entering H 3 NÁÁÁHO group and the formally sp 2 -C-atom, dedicated to form the new bond, in the furanoide transition states are consequently shorter (2,6-dimethyl-hept-5-en-2-ol: 2.08 Å , 6-methyl-hept-5-en-2-ol: 2.04 Å ) than in the pyranoide's form transition state (2,6-dimethyl-hept-5-en-2-ol: 2.16 Å , 6-methyl-hept-5-en-2-ol: 2.14 Å ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with earlier findings [18,19], the distance between the entering H 3 NÁÁÁHO group and the formally sp 2 -C-atom, dedicated to form the new bond, in the furanoide transition states are consequently shorter (2,6-dimethyl-hept-5-en-2-ol: 2.08 Å , 6-methyl-hept-5-en-2-ol: 2.04 Å ) than in the pyranoide's form transition state (2,6-dimethyl-hept-5-en-2-ol: 2.16 Å , 6-methyl-hept-5-en-2-ol: 2.14 Å ).…”
Section: Resultssupporting
confidence: 93%
“…As we investigated the possible reaction pathways already before [18,19], we focused here on a comparison of the transition states leading to the five-and sixmembered ether applying the smallest possible base NH 3 as in our earlier studies [18,19]. As alkenoles, we utilized of course 2,6-dimethyl-hept-5-en-2-ol and 6-methyl-hept-5-en-2-ol to get an impression of the influence of an extra methyl group next to OH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic studies of cycloetherifications of pent‐4‐en‐ols by treatment with PhSeCl in the presence of a base (pyridine, trimethylamine, quinolone, and 2,2'‐bipyridine) have shown that the catalytic effect of the base is caused by the hydrogen bond formed with the hydroxyl group, which increases the oxygen nucleophilic character . It has been also reported that solvents with higher polarity can better stabilize the charged transition state for the cyclization, increasing the reaction rate.…”
Section: Resultsmentioning
confidence: 99%